Tingkat Literasi Digital Mahasiswa dalam Mendeteksi Hoaks Visual di Media Sosial Instagram - Chairani Agustina; Rini Asmara (Jurnal Ragam Pengabdian, 2026)
The increasing spread of visual hoaxes on Instagram necessitates digital literacy skills for everyone, particularly students who actively use social media, especially Instagram. The purpose of this study is to identify students’ level of digital literacy in detecting visual hoaxes and assessing the credibility and authenticity of visual content. This study employs a quantitative method with a descriptive approach. The population consists of 190 students, with a sample of 66 students. Research data were collected via an online questionnaire distributed through Google Forms to students in the Library and Information Science program at Padang State University who enrolled in 2024 and 2025, using simple random sampling. The data were analyzed through validity and reliability tests and descriptive analysis using IBM SPSS Statistics software. The results of the study indicate that students’ digital literacy in detecting visual misinformation on Instagram falls into the “good” category. Students have demonstrated sufficient ability to interpret, analyze, and evaluate visual content by considering context, techniques, and the alignment between text and visuals; they are also capable of effectively searching for, evaluating, and managing digital information. This indicates that students possess the awareness and critical skills necessary to assess visual content on social media, thereby aiding them in identifying and avoiding visual hoaxes on Instagram.